RELASI DINAMIS TRILOGI METODE ISTINB?TH DALAM BAHTSUL MASAIL NU - Muhammad Adib; Muhammad Hasbulloh Huda (Jurnal Penelitian Ilmiah INTAJ, 2021)
This study focuses on the trilogy of istinb?th methods in Bahtsul Masail NU, namely the qaul? method, the ilh?q? method, and the manhaj? method. The starting point is the incorrect assumption of several researchers who quantitatively classify the fatwas of Bahtsul Masail based on the methods used. Using content analysis methods and synchronic-diachronic approaches, this study concludes that the trilogy of istinb?th methods is not a new formulation, but rather is referred to as the institutionalization of thinking tradition of NU kiais that was formed for a long time. In addition, the trilogy of intinb?th methods has a dynamic relationship and often overlaps with each other in Bahtsul Masail.